Напрямки інтеграції України до економічної моделі Європейського Союзу (на прикладі інвестиційно-інноваційної політики ЄС) - Головаш, Б. Е. (Ways to Improve Construction Efficiency, 2014)
The features of the investment and innovation policies Evropeyskogo Union at the present stage. Some measures of the state stimulation of innovative development of Ukraine, primarily through its involvement in the pan-European research programs.